Application of discrete wavelet transformation in damage detection. Part I: Static and dynamic experiments - Knitter-Piątkowska, Anna; Pozorski, Zbigniew; Garstecki, Andrzej (Computer Assisted Methods in Engineering and Science, 2022)
The paper demonstrates the potential of Discrete Wavelet Transform (DWT) in damage detection. Efficiency of the method is demonstrated by the way of examples. In this study the numerically simulated static and dynamic experiments were used. One dimensional DWT was used to signal processing. Measurement errors were accounted for by introduction of white noise.